Effects of different habitual foot strike patterns on in vivo kinematics of the first metatarsophalangeal joint during shod running—a statistical parametric mapping study - Wu, Kaicheng; Sun, Xiaole; Ye, Dongqiang; Zhang, Faning; Zhang, Shen; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2023)
Existing studies on the biomechanical characteristics of the first metatarsophalangeal joint (1 st MTPJ) during shod running are limited to sagittal plane assessment and rely on skin marker motion capture, which can be affected by shoes wrapping around the 1 st MTPJ and may lead to inaccurate results. This study aims to investigate the in vivo effects of different habitual foot strike patterns (FSP) on the six degrees of freedom (6DOF) values of the 1 st MTPJ under shod condition by utilizing a dualfluoroscopic imaging system (DFIS). Long-distance male runners with habitual forefoot strike (FFS group, n = 15) and rearfoot strike (RFS group, n = 15) patterns were recruited. All participants underwent foot computed tomography (CT) scan to generate 3D models of their foot. The 6DOF kinematics of the 1 st MTPJ were collected using a DFIS at 100 Hz when participants performed their habitual FSP under shod conditions. Independent t-tests and one-dimensional statistical parametric mapping (1-d SPM) were employed to analyze the differences between the FFS and RFS groups' 1 st MTPJ 6DOF kinematic values during the stance phase. FFS exhibited greater superior translation (3.5−4.9 mm, p = 0.07) during 51%-82% of the stance and higher extension angle (8.4°-10.1°, p = 0.031) during 65%-75% of the stance in the 1 st MTPJ than RFS. Meanwhile, FFS exhibited greater maximum superior translation (+3.2 mm, p = 0.022), maximum valgus angle (+6.1°, p = 0.048) and varus-valgus range of motion (ROM) (+6.5°, p = 0.005) in the 1st MTPJ during stance. The greater extension angle of the 1 st MTPJ in the late stance suggested that running with FFS may enhance the propulsive effect. However, the higher maximum valgus angle and the ROM of varus-valgus in FFS may potentially lead to the development of hallux valgus. Introduction